EFFECT OF SPRAYING OF PROSOPIS FARCTA EXTRACT, FOLICIST AND ABO NAJEMH20 ON GROWTH OF POMEGRANATE TRANSPLANT VAR. WONDERFUL CALIFORNIA - NABI, HASAN SALEEM (Journal of Duhok University, 2021)
This investigation was carried out during growing season (2019-2020) in the lathhouse of College of Agricultural Engineering Sciences, University of Duhok, Kurdistan region, Iraq. To investigate the effect of spraying with Prosopis farcta (0, 100 and 200 ppm), Folicist (0, 50, and 100 ppm) and Abo-najemh20 (50, 75 and 150 ppm) on growth of Pomegranate transplant. The results show that the all studied parameters were increased by increasing the concentration of Prosopis farcta especially at (200 ppm) and Folicist at (100ppm) and Abo-najemh20 at (150ppm). The best interaction between Prosopis farcta and Folicist was (200ppm and 100 ppm) respectively. Also, the interaction of Prosopis farcta at 200ppm with Abo-najemh20 at 150ppm lead to enhancing most studied characteristics. And the interaction between Folicist at 100ppm + 150ppm had a significant difference in improving the studied parameters. However, in triple combinations it found that the Prosopis farcta at 200ppm + Folicist at 100ppm + Abo najemh20 at 150ppm was superior interaction compared with all other combination treatment including control treatment